Identification of Thermal Decomposition Products and Reactions for Liquid Ammonium Nitrate on the Basis of Ab Initio Calculation. Issue 2 (13th December 2016) - Izato, Yu‐Ichiro; Koshi, Mitsuo; Miyake, Atsumi
ABSTRACT: This work analyzed the thermal decomposition of ammonium nitrate (AN) in the liquid phase, using computations based on quantum mechanics to confirm the identity of the products observed in past experimental studies. During these ab initio calculations, the CBS‐QB3//ωB97XD/6–311++G(d, p) method was employed. It was found that one of the most reasonable reaction pathways is HNO3 + NH4 + → NH3 NO2 + + H2 O followed by NH3 NO2 + + NO3 – → NH2 NO2 + HNO3 . In the case in which HNO3 accumulates in the molten AN, alternate reactions producing NH2 NO2 are HNO3 + HNO3 → N2 O5 + H2 O and subsequently N2 O5 + NH4 + → NH2 NO2 + H2 O. In both scenarios, HNO3 plays the role of a catalyst and the overall reaction can be written as NH4 + + NO3 – (AN) → NH2 NO2 + H2 O. Although the unimolecular decomposition of NH2 NO2 is thermodynamically unfavorable, water and bases both promote the decomposition of this molecule to N2 O and H2 O. Thus AN thermal decomposition in the liquid phase can be summarized as NH4 + + NO3 – (AN) → N2 O + 2H2 O.